Retention of English language tension in multilingual communities of Nepal: A review of teachers’ narratives - Rana, Karna (Journal of NELTA, 2018)
This article discusses the voices of teachers about shifting from Nepali to English medium in community schools in Nepal and suggests ways to solve some of the problems of the English language in schools of multilingual communities. The article is based on previously published teachers’ narratives in several issues of ELT Choutari web magazine in the past ten years. The teachers’ narratives, which are discussed in this article, focused on English language teaching pedagogies in Nepali government schools. The article analyses the problems, which several teachers raised in their narrative articles, and offers some suggestions to overcome them. The article begins with a discussion about the multilingual context of Nepal, language policy and the English language in schools. Moreover, the article discusses community schools’ interest in the English language, teachers’ perceptions of English as a medium of instruction and schools’ expectations of improving educational quality.